2007
DOI: 10.1136/bjsm.2007.044024
|View full text |Cite
|
Sign up to set email alerts
|

MRI study of the size, symmetry and function of the trunk muscles among elite cricketers with and without low back pain

Abstract: This study provides new insights into trunk muscle size and function in elite cricketers, and evidence of impaired motor control in elite cricketers with LBP. Rehabilitation using a motor control approach has been shown to be effective for subjects with LBP, and this may also benefit elite cricketers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
204
5
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(225 citation statements)
references
References 68 publications
15
204
5
1
Order By: Relevance
“…In those without lumbopelvic pain, the TrA thickened 65% to 67%, while the IO thickened only 13% to 18% on average. These findings clearly demonstrate that the ADIM results in preferential changes in TrA thickness in both those with and without lumbopelvic pain and, in conjunction with previous research, 7,12,17,54,59,61 provide an element of construct validity for the ADIM as a motor control exercise that preferentially targets the TrA muscle.…”
supporting
confidence: 63%
“…In those without lumbopelvic pain, the TrA thickened 65% to 67%, while the IO thickened only 13% to 18% on average. These findings clearly demonstrate that the ADIM results in preferential changes in TrA thickness in both those with and without lumbopelvic pain and, in conjunction with previous research, 7,12,17,54,59,61 provide an element of construct validity for the ADIM as a motor control exercise that preferentially targets the TrA muscle.…”
supporting
confidence: 63%
“…Many studies that have reported muscle asymmetry and strength, have associated these features with the increase of unilateral training [43][44][45]. Similar to this, we expected that thickness asymmetries would be attributed to the increased use of one hand over the other in everyday activities.…”
Section: Discussionsupporting
confidence: 67%
“…On the other hand, the CSA/LBM 2/3 values of PM and HAM tended to be higher in the sprinters of both genders as compared to the other athletic groups. For adult populations, it has been shown that athletes exhibit specific adaptations to their own competitive styles and/or training regimens in the size of muscles located in the limbs (Kanehisa et al, 1998(Kanehisa et al, , 1999 and trunk (Engstrom et al, 2007;Hides et al, 2008;Kubo et al, 2007). This is true for adolescent athletes (Hoshikawa et al, 2010).…”
Section: Discussionmentioning
confidence: 95%